Isoscalar giant resonance studies in a stored-beam experiment within EXL. (26th November 2015) - Zamora, J C; Bagchi, S; Bönig, S; Csatlós, M; Dillmann, I; Dimopoulou, C; Egelhof, P; Eremin, V; Furuno, T; Geissel, H; Gernhäuser, R; Harakeh, M N; et al.
Abstract: In the first campaign of the exotic nuclei studied with light-ion induced reaction in storage rings (EXL) collaboration at the existing storage ring experimental heavy-ion storage ring (ESR) at Helmholtz Center for Heavy Ion Research (GSI), we performed the first experiments using a stored beam of 58 Ni and an internal helium gas-jet target aiming for the investigation of isoscalar giant resonances in inverse kinematics. In this experiment, inelastically scattered recoil particles (at very forward angles, °) were detected with a dedicated setup, including ultra-high vacuum (UHV)-compatible double-sided silicon strip detector (DSSDs). Preliminary results show evidence for the excitation of the isoscalar giant monopole resonance (ISGMR) in the 58 Ni nucleus. This opens the opportunity to study in the near future giant resonances also with stored radioactive beams, like 56 Ni, and extract important information about the nuclear matter incompressibility. In the present work the current status of the data analysis and results are shown and discussed.